2013
DOI: 10.1002/ps.3503
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of superoxide dismutase in oxidative stress in the oriental fruit fly,Bactrocera dorsalis: molecular cloning and expression profiles

Abstract: These different expression profiles suggest that the four BdSODs play different roles and respond to different oxidative stresses in B. dorsalis. Some BdSODs undergo specific reaction in the response to specific oxidative stresses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 67 publications
2
14
0
Order By: Relevance
“…On the other hand, Sod2 gene expression was attenuated suggesting lower mitochondrial metabolic activity. Our results confirm that different isoforms of SOD could respond to pollution derived stress in a different manner depending on both doses and combinations of heavy elements to which it is exposed (Tang et al, 2012;Gao et al, 2013;Won et al, 2014).…”
Section: Archives Of Insect Biochemistry and Physiologysupporting
confidence: 78%
See 1 more Smart Citation
“…On the other hand, Sod2 gene expression was attenuated suggesting lower mitochondrial metabolic activity. Our results confirm that different isoforms of SOD could respond to pollution derived stress in a different manner depending on both doses and combinations of heavy elements to which it is exposed (Tang et al, 2012;Gao et al, 2013;Won et al, 2014).…”
Section: Archives Of Insect Biochemistry and Physiologysupporting
confidence: 78%
“…Hydrogen peroxide is decomposed to water and oxygen by the action of catalase (CAT). It was observed that gene expression and activity of antioxidative enzymes changes as a response to various environmental stresses both in vertebrates (Hansen et al, 2006) and invertebrates (Roh et al, 2006;Vlahogianni et al, 2007), including insects (Tang et al, 2012;Gao et al, 2013;Won et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, expression of SOD2 was sharply increased under cold stress but was reduced under heat stress. It may be that SOD2 (MnSOD), which is located in the mitochondria, has a specific response to various degrees of destruction of mitochondria induced by temperature stress (Dawson et al, 2015;Gao et al, 2013). Overall, the antioxidant enzyme system in Q. spinosa was activated and could protect the liver from the thermal stress-induced oxidative stress (Meng et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…When insects suffer from environmental stresses such as extreme temperatures, reactive oxygen species (ROS) are spawned (Gao XM et al, 2013). Metalloenzyme SOD is the most effective intracellular enzymatic antioxidant which is ubiquitous in all aerobic organisms and in all subcellular compartments prone to ROS mediated oxidative stress.…”
Section: Discussionmentioning
confidence: 99%